Negative prognostic significance of primary cilia and cytoplasmic β-catenin expression in non-small cell lung cancer - Rosova, Blanka; Filipova, Alzbeta; Hadzi Nikolov, Dimitar; Drösslerova, Marie; Matej, Radoslav; Rozsypalova, Aneta; Richter, Igor; Melichar, Bohuslav; Mahel, Rostislav; Stepanova, Radka; Lohynska, Radka; Dvorak, Josef (Neoplasma, 2024)
The objective of this study was to investigate the prognostic significance of the frequency of primary cilia (PC) and β-catenin expression in 218 patients (pts) with non-small cell lung cancer (NSCLC), including 125 pts with adenocarcinoma and 93 pts with squamous cell carcinoma. In the whole group of 218 pts with NSCLC, overall survival (OS) was significantly inferior among pts with present PC than without PC (p=0.024) and with higher cytoplasmic β-catenin expression (25-75%) than with lower cytoplasmic β-catenin expression (<25%) (p=0.008). In the univariate Cox proportional hazard model, the hazard ratio was 1.653 in pts with present PC (p=0.026) and 1.851 in pts with higher cytoplasmic β-catenin (25-75%) (p=0.009). Multivariate testing of the whole group of 218 pts with NSCLC showed that the presence of PC was associated with a worse prognosis (p=0.018). In the subgroup of 125 pts with adenocarcinoma, OS was significantly improved in pts with higher membranous β-catenin expression (≥50%) than in pts with lower expression (<50%) (p=0.0300) and OS was significantly inferior in pts with higher cytoplasmic β-catenin expression (25-75%) than in pts with lower expression (<25%) (p=0.0004). Multivariate testing of the subgroup of pts with adenocarcinoma showed that cytoplasmic β-catenin (p<0.001) and pleural invasion (p=0.017) were associated with worse prognosis. The present results indicate a negative prognostic significance of PC and cytoplasmic β-catenin expression in NSCLC and a negative prognostic significance of cytoplasmic β-catenin expression in adenocarcinoma.
Keywords: Adenocarcinoma; nádory plic; cilie; nemalobuněčný karcinom plic; Lung Neoplasms; Humans; lidé středního věku; beta-katenin; Carcinoma, Non-Small-Cell Lung; Biomarkers, Tumor; Female; Aged; dospělí; senioři; lidé; Cilia; nádorové biomarkery; Adult; ženské pohlaví; Male; Middle Aged; Cytoplasm; prognóza; Aged, 80 and over; beta Catenin; cytoplazma; senioři nad 80 let; adenokarcinom; spinocelulární karcinom; Carcinoma, Squamous Cell; míra přežití; mužské pohlaví; Prognosis; Survival Rate